2016
DOI: 10.18203/2394-6040.ijcmph20162573
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of impact of educational intervention on knowledge and practice regarding breast self-examination among paramedical workers in a teaching hospital Maharashtra, India

Abstract: INTRODUCTIONBreast cancer is by far the most frequent cancer among women in both developed countries and developing countries (25% of all cancers). In India, breast cancer incidence rate reported was 25.8 per lac population during 2012 and mortality rate was 12.7 per lac ranking number one killer in women.1 The American Cancer Society guidelines for early detection of breast cancer recommend yearly mammogram starting at the age of forty, clinical breast examination once in every three years for women in their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…A study which was done among clinicians in Alabama, to "assessed the impact of a brief educational intervention on the knowledge and attitudes of clinicians regarding breast cancer screening," reported that clinicians knowledge and attitudes about breast cancer screening was affected positively. 30 Another study by Avachat et al 31 to evaluate the change in knowledge among paramedical staff in a teaching hospital after an educational intervention about breast self-examination also indicated a positive change in knowledge level.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A study which was done among clinicians in Alabama, to "assessed the impact of a brief educational intervention on the knowledge and attitudes of clinicians regarding breast cancer screening," reported that clinicians knowledge and attitudes about breast cancer screening was affected positively. 30 Another study by Avachat et al 31 to evaluate the change in knowledge among paramedical staff in a teaching hospital after an educational intervention about breast self-examination also indicated a positive change in knowledge level.…”
Section: Discussionmentioning
confidence: 96%
“…This positive impact of a brief educational intervention on knowledge level of cancer has been reported in other studies involving other healthcare staff. 29,30 To the best of our knowledge, no studies among community pharmacists on the impact of a brief educational intervention has been researched. A study which was done among clinicians in Alabama, to "assessed the impact of a brief educational intervention on the knowledge and attitudes of clinicians regarding breast cancer screening," reported that clinicians knowledge and attitudes about breast cancer screening was affected positively.…”
Section: Discussionmentioning
confidence: 99%